Utilization of Travel Reimbursement in the Veterans Health Administration. Issue 2 (29th July 2013) - Nelson, Richard E.; Hicken, Bret; Cai, Beilei; Dahal, Arati; West, Alan; Rupper, Randall
Abstract Purpose To improve access to care, the Veterans Health Administration (VHA) increased its patient travel reimbursement rate from 11 to 28.5 cents per mile on February 1, 2008, and again to 41.5 cents per mile on November 17, 2008. We identified characteristics of veterans more likely to receive travel reimbursements and evaluated the impact of these increases on utilization of the benefit. Methods We examined the likelihood of receiving any reimbursement, number of reimbursements, and dollar amount of reimbursements for VHA patients before and after both reimbursement rate increases. Because of our data's longitudinal nature, we used multivariable generalized estimating equation models for analysis. Rurality and categorical distance from the nearest VHA facility were examined in separate regressions. Findings Our cohort contained 214, 376 veterans. During the study period, the average number of reimbursements per veteran was higher for rural patients compared to urban patients, and for those living 50‐75 miles from the nearest VHA facility compared to those living closer. Higher reimbursement rates led to more veterans obtaining reimbursement regardless of urban‐rural residence or distance traveled to the nearest VHA facility. However, after the rate increases, urban veterans and veterans living <50 miles from the nearest VHA facility increased their travel reimbursement utilization slightly more than other patients. Conclusions Our findings suggest an inverted U‐shaped relationship between veterans' utilization of the VHA travel reimbursement benefit and travel distance. Both urban and rural veterans responded in roughly equal manner to changes to this benefit.